Associations between the number of natural teeth in postmenopausal women and hormone replacement therapy. (December 2016) - Han, Kyungdo; Ko, Youngkyung; Park, Yong-Gyu; Park, Jun-Beom
Highlights: This study investigated the relationship between the number of teeth in postmenopausal women and the use of hormone replacement therapy using nationally representative Korean data. The analysis revealed that the use of hormone replacement therapy in postmenopausal women showed positive effects for retention of natural teeth. Lack of hormone replacement therapy may be considered to be an independent risk indicator for tooth loss in Korean postmenopausal women. Abstract: Objectives: Increasing research suggests that periodontal status is associated with hormone replacement therapy in postmenopausal women. This study was performed to assess the relationship between the number of natural teeth and ever use of hormone replacement therapy in postmenopausal women using nationally representative Korean data. Methods: Data from the Korea National Health and Nutrition Examination Survey between 2010 and 2012 were used, and the analysis in this study was confined to a total of 4869 respondents over 19 years old who had gone through menopause and who had no missing data for the reproductive factors and outcome variables in that study. The total number of natural teeth was then calculated after excluding third molars. The time of day when tooth brushing was done was recorded as representative oral health behavior. Multiple logistic regression analyses were used to assess association between the number of natural teeth and the use of hormone replacement therapy. Results: Among participants who had ever used hormone replacement therapy, the proportions (percentage and standard error) with no teeth, 1–9 teeth, 10–19 teeth, 20–27 teeth, and 28 teeth were 5.0 ± 2.4%, 6.7 ± 1.4%, 12.5 ± 1.7%, 18.9 ± 1.0%, and 20.7 ± 1.6%, respectively ( P   <  0.05). The adjusted odds ratio and 95% confidence interval for having fewer than 20 teeth <20 was 0.624 [0.464–0.840] for the individuals using hormone replacement therapy, after adjustments. Conclusions: The analysis revealed that the use of hormone replacement therapy by postmenopausal women showed positive effects for retention of natural teeth. Lack of hormone replacement therapy may be considered to be an independent risk indicator for tooth loss in Korean postmenopausal women.